Legislative Legal Politics of Inheritance Law in Indonesia - ., Zuhrah; Handayani, I Gusti Ayu Ketut Rachmi; Harahap, Burhanuddin (Journal of Ecohumanism, 2024)
This article is the result of research on the legal politics of inheritance law legislation in Indonesia. This study employs normative research methods, focusing on literature review and legal documents to understand the principles and regulations in force. Through the approach of case analysis, legislative analysis, and an examination of legal politics in Indonesia, the research delves into the relevant aspects. Data analysis was used to identify and understand legal norms related to inheritance distribution within the systems of customary law, Islamic law, and civil law in Indonesia. The research findings indicate that there are still many cases of inheritance disputes in Indonesia due to the ongoing discrepancies between Islamic law and customary law, civil law and Islamic law, as well as customary law and Islamic law, which leads to conflict. This can be observed through the increasing number of cases submitted regarding inheritance disputes, whether in religious courts, district courts, or handled through customary law mechanisms in Indonesia each year. However, civil law can be considered an alternative in addressing inheritance law issues in Indonesia. This is evident in the civil inheritance distribution system, which is considered fair, without discrimination between men and women